Pengembangan Career Adaptability Melalui Inovasi Sumber Daya Manusia - Hasanah, Rizkiyah; Munawwaroh, Izzatul; Qushwa, Febriyanti Ghayatul; Agus R, Abu Hasan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This article discusses the development of career adaptability through human resource innovation at MA Bahrul Ulum Besuk. This research uses a qualitative case study approach, the research subjects consist of the Principal and several Deputy Heads. Data collection techniques use interviews, documentation, observation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The focus of this research is that researchers want to describe Career Adaptability Development through Human Resource Innovation at MA Bahrul Ulum Besuk. This research data was obtained through interviews, observation and documentation. In the next stage, researchers checked the validity of the data by extending participation, diligent observation and triangulation. To get more accurate and accountable results, researchers conducted interviews with the Principal, Deputy Head of Student Affairs, Deputy Head of Curriculum and Teachers at MA Bahrul Ulum Besuk. The research results show that Career Adaptability Development through Human Resources innovation at MA Bahrul Ulum Besuk can be successfully carried out through human resource innovation by focusing on the dimensions of concern, control, curiosity and confidence. The implementation of a holistic career development program has proven its effectiveness in building self-confidence and readiness to face career changes. Regular monitoring of student skills and achievements provides a clear picture of the development of skills relevant to the world of work, enabling the identification of individual potential and the provision of constructive feedback. In addition, career resource centers are an important platform in providing the information, training and support needed to develop career adaptability. Overall, human resource innovation in the form of career programs, skills and achievement monitoring, and the role of career resource centers make a positive contribution in shaping individual career adaptability, creating a solid foundation for successful navigation in a dynamic world of work.